Mortality gap for people with bipolar disorder and schizophrenia: UK-based cohort study 2000–2014. (September 2017) - Hayes, Joseph F.; Marston, Louise; Walters, Kate; King, Michael B.; Osborn, David P. J.
Abstract : Background: Bipolar disorder and schizophrenia are associated with increased mortality relative to the general population. There is an international emphasis on decreasing this excess mortality. Aims: To determine whether the mortality gap between individuals with bipolar disorder and schizophrenia and the general population has decreased. Method: A nationally representative cohort study using primary care electronic health records from 2000 to 2014, comparing all patients diagnosed with bipolar disorder or schizophrenia and the general population. The primary outcome was all-cause mortality. Results: Individuals with bipolar disorder and schizophrenia had elevated mortality (adjusted hazard ratio (HR) = 1.79, 95% CI 1.67–1.88 and 2.08, 95% CI 1.98–2.19 respectively). Adjusted HRs for bipolar disorder increased by 0.14/year (95% CI 0.10–0.19) from 2006 to 2014. The adjusted HRs for schizophrenia increased gradually from 2004 to 2010 (0.11/year, 95% CI 0.04–0.17) and rapidly after 2010 (0.34/year, 95% CI 0.18–0.49). Conclusions: The mortality gap between individuals with bipolar disorder and schizophrenia, and the general population is widening.